IMPROVEMENT OF THE OPERATIONAL PROPERTIES OF ETHANOL MOTOR FUELS BY MICRODOSES OF CARBON SPHEROIDAL NANOCLUSTERS - Гайдай, О. О.; Пилявський, В. С.; Полункін, Є. В. (Science-based technologies, 2016)
In the paper evidence-based compounding of alternative fuel with the high content of an oxygenate (ethyl alcohol ~ 85%) and spheroidal nanodimensional carbon clusters as the modifying additives is for the first time carried out. The unusual fact of increase of the pressure of saturated steam (PSS) with addition of nanocarbon clusters of CNOs is investigated. Extreme dependence of PSS on hold time of fuel with the specified additive is established. It is determined that the created alternative fuels on the antiwear properties prevail over usual oil fuels thanks to effect of structurization as a result of action of the nanostructural centers. It is proved that additives of nanocarbon clusters of CNOs in mixed fuels effectively slow down corrosion processes on details of the fuel equipment and cylinder-piston group of engines. The carried-out motor tests of the fuels developed that the mixed fuel in comparison with oil A-95 gasoline have shown essential advantages of alternative fuels on the key operational parameters: increase in value of the maximum torque, effective efficiency, reduction of specific effective fuel consumption and toxic emissions.